2020
DOI: 10.1111/mpp.13015
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule‐assisted mechanism for toxisome assembly in Fusarium graminearum

Abstract: In Fusarium graminearum, a trichothecene biosynthetic complex known as the toxisome forms ovoid and spherical structures in the remodelled endoplasmic reticulum (ER) under mycotoxin‐inducing conditions. Previous studies also demonstrated that disruption of actin and tubulin results in a significant decrease in deoxynivalenol (DON) biosynthesis in F. graminearum. However, the functional association between the toxisome and microtubule components has not been clearly defined. In this study we tested the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In HeLa cell, MT is crucial for the spatial distribution and biological functions of purinosomes [ 43 ]. Our recent study demonstrated that MT participated in toxisomes formation and DON biosynthesis in F. graminearum [ 44 ]. In this work, we analyzed the regulatory role of MT network in vacuole morphology via carbendazim treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HeLa cell, MT is crucial for the spatial distribution and biological functions of purinosomes [ 43 ]. Our recent study demonstrated that MT participated in toxisomes formation and DON biosynthesis in F. graminearum [ 44 ]. In this work, we analyzed the regulatory role of MT network in vacuole morphology via carbendazim treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that fragmented vacuoles could facilitate FB 1 biosynthesis, yet there is no close correlation between the expression levels of FvFum1 and vacuole morphology in F. verticillioides . Additionally, in F. graminearum , low concentrations of carbendazim boosted DON production, but high concentrations significantly reduced it [ 44 ]. Our experiments utilized a 1 μg/mL carbendazim concentration, resulting in increased FB1 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of β 1 -or β 2 -tubulin (Δβ 1 and Δβ 2 mutants) did not affect microtubule assembly in F. graminearum (33). Moreover, recent studies showed that Δα 1 , Δα 2 , Δβ 1 and Δβ 2 mutants play different roles in toxisome formation of F. graminearum (34). The different phenotypes implied that α 1 -, α 2 -, β 1 -, and β 2 -tubulin may be functionally divergent.…”
Section: Introductionmentioning
confidence: 98%
“…Fusarium graminearum is an ascomycetous fungus that is the major cause of Fusarium head blight (FHB) on wheat and barley, as well as stalk and ear rot disease on maize. This fungus not only causes crop yield and quality losses but also contaminates grain with mycotoxins, rendering them unfit for food or feed (Etzerodt et al, 2016;Kim and Vujanovic, 2016;Masci et al, 2015;Zhou et al, 2021). Benzimidazoles and sterol demethylation inhibitors are widely used for the control of FHB (Blandino et al, 2006;Bian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%